Otimização da extração de compostos bioativos do gojiberry e Incorporação em nanolipossomas para aplicação em células tumorais - Peixoto, Fernanda Barroso (2023)
Gojiberry (Lycium barbarum) is a fruit that has high levels of bioactive compounds, such substances are derived from secondary metabolites produced by plants and may be related to protection against oxidative stress conditions. Due to antioxidant action, they act by preventing and inhibiting the action of free radicals in the human body, resulting in several health benefits. The high antioxidant capacity of these compounds arouses great interest in the industry, so that the extraction of these substances is essential for their application in foods, drugs and supplements. The extraction efficiency of antioxidant compounds is influenced by several factors, such as extraction technique, type of solvents, time, temperature, among others. Encapsulation methods are studied to improve the stability of extracted compounds and protect against external agents. Thus, the present work aims to optimize the extraction of bioactive compounds of Lycium barbarum and encapsulate them for application in tumor cells, evaluating the influence of solvent proportion, extraction method, time and temperature through DPPH, ABTS and Chelating ability Fe (II) methods. The gojiberry sample was extracted with ethanol/water solvents in the proportions 50:50 (v/v), 60:40 (v/v), 70:30 (v/v), 80:20 (v/v) and 90:10 (v/v). The three antioxidant activity tests indicated high antioxidant activities for the ratio of 60:40 (v/v) ethanol/water. With this proportion, the extractions were performed and the condition that presented the highest antioxidant activity for Shaker (45°C for 24 h) and ultrasound (45°C for 6 min) were determined. The quantification of total phenolics and flavonoids indicated a significant difference between the methods, and the highest levels of compounds were obtained in ultrasound-assisted extraction (503.96 mg EAG 100g-1 sample and 314.64 mg EQ 100g-1 sample). In addition, the present study also aimed to evaluate the extraction kinetics of the extracts obtained, the results showed high yields for ultrasound and the Models So and Mac Donald and Pseudo Second Order presented the best adjustments for both methods. The characterization of the extract indicated the presence of functional groups present in phenolic compounds and polysaccharides and endothermic behavior. The bioactive compounds of the best extract were encapsulated in liposomes by ethanol injection with higher encapsulation efficiency for egg phosphatidylcholine, with values of 52.55%. The nanoparticle was produced using microfluidic and flow rate ratio 10 showed low polydispersity indexes (10.4%). The chaotic advection system provided increased productivity, presenting low diameters for the extract encapsulated with total flow rate 5 mL min-1. The cytotoxic action of the free extract produced by Shaker and ultrasound were evaluated and indicated antiproliferative activity for liver tumor cells and presented lower cellular viability for ultrasound. The encapsulation of the extract proved to be efficient in the delivery of assets presenting low cellular viability when compared to the free extract, with values of 48.19%.